2006
DOI: 10.1159/000096600
|View full text |Cite
|
Sign up to set email alerts
|

Non-Compaction on Autopsy in Duchenne Muscular Dystrophy

Abstract: Left ventricular hypertrabeculation (LVHT) /non-compaction is frequently associated with neuromuscular disorders. Recently, LVHT has been detected in a 28-year patient with Duchenne muscular dystrophy. Here, the patho-anatomic findings of this patient are presented, which showed LVHT located within in the apex and the anterior and lateral wall, being the most demanded segments during systole. The septum and the left ventricular outflow tract were not involved. The patho-anatomic specimen also showed aberrant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…Presumably, the NCCM diagnosis is often missed because many physicians are not familiar with this disease. Non‐compaction is seen predominantly in the LV wall . In our study, we found that fetal NCCM is predominantly a disease of the LV but can be seen in the RV or in both ventricles; this is in contrast to the almost exclusive involvement of the left ventricle in adults.…”
Section: Discussioncontrasting
confidence: 56%
“…Presumably, the NCCM diagnosis is often missed because many physicians are not familiar with this disease. Non‐compaction is seen predominantly in the LV wall . In our study, we found that fetal NCCM is predominantly a disease of the LV but can be seen in the RV or in both ventricles; this is in contrast to the almost exclusive involvement of the left ventricle in adults.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to our case, the reported cases of spontaneous LV noncompaction developing in adults with Becker and Duchenne muscular dystrophy and a previously normally compacted LV 15 , 16 should be noted as still other opposing arguments to the developmental inhibition theory.…”
supporting
confidence: 51%
“…Echocardiography classically shows patterns of dilated cardiomyopathy. However, cases of left ventricle non-compaction have been reported in DMD [22]. Cardiac thrombus and cerebral infarction are rarely reported, mainly in DMD patients with severe heart failure [23].…”
Section: Cardiomyopathy Arrhythmia and Conduction Abnormalitiesmentioning
confidence: 99%